Effect of Alcoholic Extract of Bark of Terminalia arjuna (Roxb. ex. DC) on Mast Cell Degranulation - PRASAD, M.V.V.; BALAKRISHNA, K.; WILLIAM CAREY, M. (Asian Journal of Chemistry, 2010)
The effect of the alcoholic extract of the bark of Terminalia arjuna on mast cell degranulation (in vitro study) was carried out by the modification method of Kaley and Weiner. Under the experimental conditions about 24 % of mast cells are normally degranulated. The mast cell degranulator, compound 48/80 (p-methoxy-N-methyl phenethylamine) produced about 57 % of degranulation. Pretreatment with alcoholic extract of Terminalia arjuna had shown a significant protection against the degranulation induced by compound 48/80. The protection was also evidenced by pretreatment with disodium chromoglycate a potent mast cell stabilizing agent.